The epistemological lesson in contemporary Arab thought - Mohamed, Salaa; Ahmed, Kaabouche (The International tax journal, 2026)
The purpose of this study is to demonstrate that Arab philosophical thought, whether the Western or the Eastern Arab world, responds to the necessity of engagement in epistemological inquiry despite differences in its referential frameworks, foundations, and objectives. This engagement falls within a critical project that bears an Arab imprint on scientific knowledge through diverse intellectual approaches and conceptualizations. Although it often emulates Western thought, laden with ideological presuppositions, it nonetheless articulates a philosophical vision that mobilizes the contemporary epistemic apparatus to reread Arab heritage, long resistant to critique and analysis. These are, therefore, critical intellectual projects in the process of formation and consolidation, which require an in-depth and grounded reading, given the richness of this field in concepts and procedural tools. This, in turn, underscores the paramount importance of epistemological inquiry for the Arab intellect.